Profile of Psychopharmaceutical Drug Use among Clients at the Baddoka Makassar National Narcotics Board Rehabilitation Centre - Fajriansyah, Fajriansyah; Andi Paluseri; Vina Jihanita Eka Putri (Jurnal EduHealth, 2023)
Baddoka Makassar National Narcotics Board Rehabilitation Center is one of the institutions with rehabilitation missions and functions to provide treatment, care and recovery to drug addicts or victims. Rehab clients typically suffer from psychiatric disorders, anxiety disorders, or depression. The main treatment for this disease is psychosocial therapy and psychiatric medication. This study aims to determine the patterns of psychotropic drug use among clients of the BNN Baddoka Makassar rehabilitation center. This study is a non-experimental descriptive study. A retrospective data collection was conducted from July to December 2022 which received psychopharmacological treatment and then entered the data into Microsoft Excel and then analyzed it as a percentage. The data obtained showed that the most commonly used psychiatric drug was fluoxetine, an SSRI antidepressant monotherapy, at 12.13%. The most common psychotropic combination was risperidone and trihexyphenidyl (9.24%).